Osteophyte-induced dysphagia: report of three cases - Ozgocmen, S; Kiris, A; Kocakoc, E; Ardicoglu, O (Editions Scientifiques Medicales Elsevier, 2002)
Dysphagia is a common complaint of patients seen by physicians. Osteophyte compression due to diffuse idiopathic skeletal hyperostosis (DISH) or Forestier's disease and cervical spondylosis has been identified as a cause of dysphagia. We report three elderly male cases of whom two had dysphagia due to DISH and one had dysphagia due to osteophyte compression associated with severe cervical spondylosis. Clinical and radiographical findings including barium oesophagogram and computed tomography are presented. Endoscopy should be carefully performed to rule out additional pathology in such patients. Medical treatment preferably with liquid forms of NSAIDs and diet may cause satisfactory improvement.
Keywords: diffuse idiopathic skeletal hyperostosis; dysphagia; osteophyte